Function and Use of Roman Pottery: A Quantitative Method for Assessing Use-Wear - Banducci, Laura (Journal of Mediterranean Archaeology, 2014)
The study of ceramic function, use, and re-use is becoming an important facet of the archaeology of the ancient Mediterranean. The abundant and detailed ceramic typologies of classical archaeology have meant that the function of pottery is typically assumed based on vessel form. I propose a way of nuancing our understanding of ceramic function and use to reveal repetitive habitual actions: the traces of seemingly ephemeral behaviors of daily life. I introduce a method for the empirical study of ceramic use through the application of ‘alteration analysis’ (more commonly known as ‘use-wear analysis’): that is, the recording of accretion and attrition of the surfaces of domestic pottery. I describe a recording method to capture qualitative observations of pottery in a quantitative way. This approach allows for the generation of relatively large datasets that can be subjected to statistical analysis in order to observe real patterns of use. We can begin to make inferences about behaviors like cooking and serving, the length of ceramic use-life, and the extent of ceramic consumption. I demonstrate the utility of this method with a case study of ceramics from two Republican-period sites in central Italy.